STUDI KOMPARATIF MEKANISME PERTANGGUNGJAWABAN PRESIDEN REPUBLIK INDONESIA SEBELUM DAN SESUDAH AMANDEMEN UUD 1945 - Eza Aulia (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2018)
With regard to the principle of popular sovereignty embraced by Indonesia, there is an obligation that must be done by the president as head of government to be accountable for all policies or actions related to his position to the people as the holder of the highest sovereignty, after the amendment to the constitution of the state, there is a change in the mechanism of responsibility of the president . The problem of this research is whether the similarities and material related to the mechanism of responsibility of the president before and after the amendment of the 1945 Constitution. The result of this research is that there are equations that are both doing political accountability to the people's representative institution based on the supervisory function through the right of inquiry. In contrast, there are differences in the mechanism of accountability in which before the amendment put forward the political accountability of the implementation of the GBHN, whereas after the amendment more to the legal accountability as regulated in the 1945 Constitution after the amendment. It is recommended that there be a certain regulation and mechanism related to the presidential political responsibility, so that the mechanism can assess the performance of the President against the implementation of RPJM, which has been done by the president only in the form of speech on the basis of the existing constitutional convention.Keywords : Comparison, Responsibility of the President.